PENGARUH TINGKAT KECEMASAN TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 1 NGRAMPAL SRAGEN TAHUN 2021/2022: PENGARUH TINGKAT KECEMASAN TERHADAP PRESTASI BELAJAR MATEMATIKA - SUWARNI SUWARNI (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
The article entitled "The Influence of Anxiety Level on Mathematics Learning Achievement of Class VIII Students of SMPN 1 Ngrampal Sragen 2021/2022" is a case study, where anxiety is a serious problem whose solution is not easy, because anxiety plays a major role for someone in avoiding studying and apply knowledge including mathematics. If students have high levels of anxiety then the learning process will not be meaningful for students. The result is that there is a negative influence of anxiety level (X) on mathematics learning achievement (Y). It is proven that Fregressive > Ftable is 36.3843875 > 7.096 > 4.008. This means that students who experience high anxiety will achieve less well in mathematics. Furthermore, mathematics is actually not a difficult lesson. In learning mathematics, students are required to do a lot of practice working on questions and it is hoped that students will not quickly give up if they experience difficulties in learning. The anxiety experienced can be overcome by improving the relationship between teachers and students' parents, through a persuasive approach with students who experience anxiety.